Quantum kinetic theory of metal clusters in an intense electromagnetic field - Bonitz, M.; Dufty, J.W. (Condensed Matter Physics, 2004)
A quantum kinetic theory for weakly inhomogeneous charged particle systems is derived within the framework of nonequilibrium Green’s functions. The results are of relevance for valence electrons of metal clusters as well as for confined Coulomb systems, such as electrons in quantum dots or ultracold ions in traps and similar systems. To be specific, here we concentrate on the application to metal clusters, but the results are straightforwardly generalized. Therefore, we first give an introduction to the physics of correlated valence electrons of metal clusters in strong electromagnetic fields. After a brief overview on the jellium model and the standard density functional approach to the ground state properties, we focus on the extension of the theory to nonequilibrium. To this end a general gauge-invariant kinetic theory is developed. The results include the equations of motion of the two-time correlation functions, the equation for the Wigner function and an analysis of the spectral function. Here, the concept of an effective quantum potential is introduced which retains the convenient local form of the propagators. This allows us to derive explicit results for the spectral function of electrons in a combined strong electromagnetic field and a weakly inhomogeneous confinement potential. На основі нерівноважних функцій Гріна розроблено квантову теорію слабонеоднорідної системи заряджених частинок. Отримані результати мають суттєве значення для опису валентних електронів металічних кластерів, а також для замкнутих кулонівських систем, таких як електрони в квантових точках чи ультрахолодні іони в пастках. Зокрема, в даній роботі ми зупиняємося на розгляді металічних кластерів, хоча результати можна безпосередньо узагальнити на інші випадки. Ми розпочинаємо з введення в фізику скорельованих валентних електронів у металічних кластерах в сильних електромагнітних полях. Після короткого огляду моделі “желе” та стандартного методу функціоналу густини для опису основних станів ми зосереджуємося на узагальненні теорії на випадок нерівноважних процесів. З цією метою розроблено узагальнену калібрувально-інваріантну кінетичну теорію. Ці результати включають рівняння руху для двочасових кореляційних функцій, рівняння для функцій Вігнера та аналіз спектральної функції. Вводиться поняття ефективного квантового потенціалу, який залишає незмінною локальну форму пропагаторів. Це дає нам змогу отримати явні вирази для спектральної функції електронів при суперпозиції сильного електромагнітного поля та слабонеоднорідного утримуючого потенціалу.